Education with Class League as A Strategy to Improve Student Learning Metacognition - Novega Pratama Adiputra (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study aims to improve learning outcomes by applying the Education with Class League learning model which can make a major contribution to learning which will make students better understand their own abilities, be more active in asking questions, answering questions, giving responses or opinions, discussing well and being able to understand the concept of subject matter well. In addition, students can find various strategies to monitor and check their understanding. The achievement of the objectives of this study used a research and development model that used class XI students at SMA Negeri 6 Madiun using three different materials. Based on the results of trials that have been done, it can be concluded that the use of this ECL model can improve students' learning metacognition. This can be proven by looking at student learning outcomes that are better than before the use of the ECL model in the learning process. In addition, there was also an increase in the percentage of completeness both from the affective, psychomotor, and cognitive aspects. In the learning process, students also feel motivated and have high enthusiasm for participating in all learning activities, and students can measure their own ability to understand a learning material.